2013
DOI: 10.2147/cia.s47263
|View full text |Cite
|
Sign up to set email alerts
|

Echo intensity obtained from ultrasonography images reflecting muscle strength in elderly men

Abstract: BackgroundIt is well known that loss of muscle mass (quantitative change) is a major change that occurs with aging. Qualitative changes in skeletal muscle, such as increased intramuscular fat, also occur as one ages. Enhanced echo intensity (EI) on ultrasonography images of skeletal muscle is believed to reflect muscle quality. Recent studies evaluating the quality of skeletal muscle using computer-aided gray scale analysis showed that EI is associated with muscle strength independently of age or muscle size i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
273
9
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 249 publications
(320 citation statements)
references
References 32 publications
26
273
9
12
Order By: Relevance
“…It has been reported that the fat mass of the thigh muscle in sarcopenia is increased compared to non sarcopenia. 12,13,14 Indeed, body fat percentage/weight was also significantly higher in the sarcopenia group in this study.…”
Section: Discussionsupporting
confidence: 59%
“…It has been reported that the fat mass of the thigh muscle in sarcopenia is increased compared to non sarcopenia. 12,13,14 Indeed, body fat percentage/weight was also significantly higher in the sarcopenia group in this study.…”
Section: Discussionsupporting
confidence: 59%
“…Theoretically, ALM of DXA reflects whole lean tissues and not perfectly equal to SMM. In addition, muscle quality and muscle composition change with aging [50][51][52][53][54][55][56][57], but the current study does not examine these effect. As another limitation, Prado et al [58] stated that single cutoff may not suitable for all age, and they used large dataset of DXA ALM with 13,236 subjects from 1999-2004 NHANES cohort and LMS curve-fitting procedure to establish age and gender specific cutoffs.…”
Section: Discussionmentioning
confidence: 79%
“…As a representative example, Watanabe et al (50) recently observed an inverse association between echo intensity and muscle strength in elderly men.…”
Section: Ultrasoundmentioning
confidence: 99%
“…As subjects age and develop sarcopenia skeletal muscles increasingly have adipose tissue infiltration and fibrosis that lead to new sound reflection planes (49) . These changes are accompanied by an increase in echogenicity, indicated as whiter muscles in ultrasonography, and the amount of 'white' and 'dark' muscle tissue of the sonographic images can be quantified by the degree of the echolucencies in human subjects (40,50) . These effects are readily 31 P MRS provides information on high-energy intermediates and related metabolic processes.…”
Section: Ultrasoundmentioning
confidence: 99%